Bacteriology of the urethra in normal men and men with nongonococcal urethritis. - Bowie, W R (1977)
Sixty-nine Caucasian males without a previous history of urethritis and who developed nongonococcal urethritis (NGU) and 39 similar men without urethritis (NU) were cultured from the urethra for Chlamydia trachomatis, Mycoplasma hominis, Ureaplasma urealyticum, aerobes, and anaerobes. C. trachomatis infection was proven by culture of serology in 26 (38%) of the NGU group and 1 (3%) of the NU group; the C. trachomatis-negative NGU group had significantly more U. urealyticum (81%) than the C. trachomatis-positive NGU group (42%) or the NU group (59%). Aerobes were isolated from significantly more NU men (91%) than from men with NGU (66%). The aerobic and anaerobic flora of the two NGU groups were similar. The NU group had significantly more aerobic lactobacilli. Haemophilus vaginalis, alpha-hemolytic streptococci (not Streptococcus faecalis), and anaerobes, predominantly Bacteroides species. This study has provided information about the prevalence and the variety of the aerobic and anaerobic microbiological flora of the anterior urethra of sexually active males. It does not implicate any bacteria other than C. trachomatis and U. urealyticum as potential causes of NGU.